Adverse perinatal outcomes in pregnancies affected by severe COVID-19 infectionAJOG Global Reports at a Glance - Odessa P. Hamidi, MD; Virginia Lijewski, MPH; Jeanelle Sheeder, PhD; Kristin Powell, MD; Erica Dolph, BS; Delisa Quayson, MD; Shane Reeves, MD (Elsevier, 2022)
BACKGROUND: Severe COVID-19 infection in pregnancy has been associated with an increase in adverse perinatal outcomes, although studies differ regarding which outcomes are affected. Increased characterization of obstetrical and neonatal outcomes is needed, including details on indications for preterm delivery and additional neonatal adverse outcomes. OBJECTIVE: This study aimed to determine whether there is a higher rate of adverse perinatal outcomes with severe-to-critical COVID-19 infection compared with nonsevere COVID-19 diagnosed during pregnancy. STUDY DESIGN: This was a retrospective observational cohort study that compared rates of adverse perinatal outcomes between patients with severe-to-critical and those with nonsevere (asymptomatic, mild, or moderate) COVID-19 infection. Patients had singleton pregnancies and a positive laboratory polymerase chain reaction result for COVID-19. Primary outcomes included hypertensive disorders of pregnancy, cesarean delivery, fetal growth restriction, preterm birth, and neonatal intensive care unit admission. Additional neonatal outcomes analyzed included need for cardiopulmonary resuscitation, low birthweight (<2500 g), 1- or 5-minute Apgar score <7, need for supplemental oxygen, need for intubation, intraventricular hemorrhage, sepsis, respiratory distress syndrome, bronchopulmonary dysplasia, blood transfusion, necrotizing enterocolitis, hypoxic-ischemic encephalopathy, birth trauma, or neonatal death. Appropriate bivariate analyses were used to compare groups. Logistic regression was used to examine primary outcomes while adjusting for confounders. RESULTS: A total of 441 participants were identified and confirmed via detailed chart review to be pregnant with a singleton pregnancy while diagnosed with COVID-19. Of these, 44 (10%) met National Institutes of Health criteria for severe-to-critical COVID-19 infection. The median gestational age at the time of maternal COVID-19 diagnosis was 36.4 weeks (interquartile range, 29.6-38.6). Severe-to-critical COVID-19 infection had a higher risk of a composite adverse neonatal outcome (36.4% vs 21.4%; P=.03). There was a high incidence of hypertensive disorders of pregnancy overall (20.6%), but this outcome was not higher in the severe-to-critical vs nonsevere group. There were no maternal deaths. There was a low incidence of neonatal COVID-19 test positivity among those tested (1.8%). When adjusting for presence of heart disease and gestational age at COVID-19 diagnosis, severe-to-critical COVID-19 was strongly associated with fetal growth restriction (adjusted odds ratio, 2.73; confidence interval, 1.03-7.25) and neonatal intensive care unit admission (adjusted odds ratio, 3.50; confidence interval, 1.56-7.87). Preterm delivery was more common but was no longer significant after adjustment (adjusted odds ratio, 2.23; confidence interval, 0.99-5.05). CONCLUSION: Severe-to-critical COVID-19 infection during pregnancy is associated with higher rates of adverse neonatal outcomes and strongly associated with neonatal intensive care unit admission and fetal growth restriction compared with nonsevere disease. There is a high rate of hypertensive disorders of pregnancy overall in all those affected by COVID-19, regardless of severity. Pregnant persons should be counseled on these risks to encourage vaccination, and those with infection during pregnancy should be monitored for fetal growth disorders.